2020
DOI: 10.1021/acs.inorgchem.0c00165
|View full text |Cite
|
Sign up to set email alerts
|

Structural Diversity in 2,2′-[Naphthalene-1,8:4,5-bis(dicarboximide)-N,N′-diyl]-bis(ethylammonium) Iodoplumbates

Abstract: Crystallization from solutions containing 2,2′-[naphthalene-1,8:4,5bis(dicarboximide)-N,N′-diyl]-bis(ethylammonium) diiodide ((NDIC2)I 2 ) and PbI 2 has been investigated. Eight different materials are obtained, either by variation of crystallization conditions or by subsequent thermal or solvent-induced transformations. Crystal structures have been determined for five materials. 5) form 1-dimensional (1D) chains consisting of PbI 6 (and, in the case of 1, PbI 5 (DMF)) octahedra, either solely facesharing or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 77 publications
5
25
0
Order By: Relevance
“…With the increase of Br content, the lamellar structure gradually becomes blurred and the crystal surface becomes smoother. For crystal 1 , the average Pb–I bond length in the inorganic chain is 3.233 Å (3.200–3.261 Å), which is the typical Pb–I bond lengths in perovskites and perovskite-like materials . The in-plane bending angle in the face-sharing octahedron is 179.7° (Figure S8), suggesting the linear conformation of the 1D inorganic chain.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…With the increase of Br content, the lamellar structure gradually becomes blurred and the crystal surface becomes smoother. For crystal 1 , the average Pb–I bond length in the inorganic chain is 3.233 Å (3.200–3.261 Å), which is the typical Pb–I bond lengths in perovskites and perovskite-like materials . The in-plane bending angle in the face-sharing octahedron is 179.7° (Figure S8), suggesting the linear conformation of the 1D inorganic chain.…”
Section: Resultsmentioning
confidence: 86%
“…For crystal 1, the average Pb−I bond length in the inorganic chain is 3.233 Å (3.200−3.261 Å), which is the typical Pb−I bond lengths in perovskites and perovskite-like materials. 31 The in-plane bending angle in the face-sharing octahedron is 179.7°(Figure S8), suggesting the linear conformation of the 1D inorganic chain. Adjacent NDIA connects by the intermolecular H-bonds formed between the hydrogen on the end of the n-butylamine with oxygen anhydride and nitrogen amide (Figure S9b) but without direct π−π stacking.…”
Section: Resultsmentioning
confidence: 99%
“…Bulkier cations have also been shown to induce distortions in the metal-halide lattice that affect the bandgap and other energetic properties . Furthermore, researchers have found that certain bulky cations tend to stabilize in even lower dimensional perovskite-like structures (i.e., corner-sharing metal-halide octahedron), such as 1D wires or 0D clusters. While these lower dimensional structures possess interesting and useful properties of their own (e.g., strong quantum confinement, size-dependent properties, and exotic structural possibilities), they can also have undesirable properties such as rapid self-trapping of excitons and shorter excited-state lifetimes . Because of the structural limitations of the layered 2D MHP lattice, the majority of organic cations that have been explored so far are either minimally branched alkyl chains (as long as eight units have been reported) or small aromatics like acenes and thiophenes.…”
Section: Structure and Modular Design Of Hybrid 2d Metal-halide Perov...mentioning
confidence: 99%
“…35−37 A recent study demonstrated numerous 0D and 1D structures formed from PbI 2 and NDIC2, where the structures could be altered by crystallization conditions or thermal-and solvent-induced transformations. 38 However, no 2D PQW structures or materials including both NDIC2 and other organic cations have yet been reported. We fabricated thin films of higher n perovskites containing NDIC2 molecules to study how they affect PQW formation, width distribution, structure, spatial ordering, and photoexcited carrier dynamics of the hybrid system.…”
Section: ■ Introductionmentioning
confidence: 99%